How effective are sovereign bond-backed securities as a spillover prevention device? - David Cronin; Peter G. Dunne (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
Brunnermeier et al. (2017) propose the introduction of sovereign bond-backed securities (SBBS) in the euro area. That and other papers assess how the securitisation would insulate senior bond holders from actual default-related losses. This paper generalises the assessment by using the VAR-based Diebold and Yilmaz (2012) spillover index methodology to assess potential attenuation of the spillover of shocks in holding-period returns across bond markets due to the introduction of SBBS. This is made possible by employing SBBS yields estimated from historical euro area member state sovereign bond yields using Monte Carlo methods, as described in Schönbucher (2003). A lower spillover o of shocks between SBBS securities compared to what arises between eleven member states' bond markets is observed. Spillover values fall during the euro area sovereign bond crisis. Gross and net spillovers are lower for a 70-30 tranching than for a 70-20-10 case but in both cases the senior tranche becomes more insulated from shocks in the more junior tranches during periods of financial stress.
Keywords: C58; G11; G12; G17; 330; Safe Assets; Sovereign Bond Securitisation; Bank-Sovereign Diabolic Loop